Framing the Mobile Phone: The Psychopathologies of an Everyday Object - MacRury, Iain; Yates, Candida (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2016)
This article proposes that the affective processes that shape our relationship to the world of digital consumption and communication can be illuminated further when viewed through a lens of object relations psychoanalysis. We focus on the use of the mobile phone as both an object in the world and of the psyche in order to reflect upon its uses as an evocative object that shapes the psychosocial boundaries of experience in everyday life. We argue that in contrast to the concepts of interpersonal communication that can be found in some domains of popular culture and in communication studies, object relations psychoanalysis can be usefully deployed in order to explore the unconscious attachments that develop in relation to consumer objects, allowing for the complexity of feeling and reflection that may emerge in relation to them and the potential spaces of the mind. The mobile phone’s routine uses and characteristics are widely understood. At the same time, the mobile phone invites critical reflections that identify a paradoxical object of both creative and pathological use. Such reflexivity includes the mobile’s relationship to the complexity of psychosocial experience within the contemporary cultural moment. Applying the ideas of psychoanalysts Donald Winnicott, Thomas Ogden and Christopher Bollas, we argue that one explanation for why the mobile phone continues to attract not only enthusiastic cultural commentary but also a degree of apprehension across academic and popular-discursive settings can be found in its capacity to both disrupt and connect as an object of attachment and as a means of unconscious escape.
Keywords: transitional object; potential space; Pathology; mobile phones; object relation psychoanalysis